Clinical study on S-1108 in the treatment of respiratory tract infections - Yamaguchi Etsuro; Kawakami Yoshikazu (CHEMOTHERAPY, 1993)
To evaluate the usefulness of the novel and oral esterified cephem antibiotic S-1108 in respiratory infections, we conducted a clinical trial. The study subjects included 5 patients with respiratory tract infection (1 male and 4 females; age, 34 to 69 yr). S-1108 was administered orally in doses of 100 to 200 mg t. i. d. for 3 to 14 days. Clinical effects were good in 2 cases, fair in 2, and poor in 1. The overall efficacy rate was 2/5. No side effects or abnormal laboratory data were observed. 新しく開発されたエステル型経口セフェム系抗生物質であるS-1108の呼吸器感染症に対する有用性を検討する目的で, 臨床的検討を行った。対象は呼吸器感染症5例で, 疾患は急性気管支炎4例と急性細菌性肺炎1例である。本剤の投与方法は1回100mg～200mgを1日3回毎食後に経口投与した。投与量は300mg/日が3例, 450mg/日が1例および600mg/日が1例で, 投与期間は3～14日であった。臨床成績は5例中有効2例, やや有効2例, 無効1例で有効率2/5であった。副作用および臨床検査値異常は1例も見られなかった。